Correlation between asparaginase enzyme activity levels and coagulation parameters during childhood acute lymphoblastic leukemia treatment. Issue 2 (15th November 2022) - Højfeldt, Sofie Gottschalk; Grell, Kathrine; Hvitfeldt, Lone; Wehner, Peder Skov; Bjerre, Jesper; Albertsen, Birgitte Klug
Abstract: Thromboembolism is a serious toxicity in the treatment of acute lymphoblastic leukemia (ALL), but little is known about the correlation between asparaginase enzyme activity (ASA) levels and coagulation parameters. We included 65 non‐high risk ALL patients, aged 1–17 years. Coagulation parameters and corresponding ASA levels were measured during asparaginase treatment. We found ASA to be negatively correlated with antithrombin and fibrinogen up to ASA levels of 250 IU/L, after which these parameters reached a plateau and did not decrease further with further increase of ASA. Patients with silent inactivation of asparaginase had normal coagulation parameters.